Instantaneous correlations of Shannon’s big data in nonlocal cosmos - Bulyzhenkov, Igor É. (Frontiers in Astronomy and Space Sciences, 2025)
The etheric energy in Umov’s thermomechanical transport through material space changes reversibly within a limited band of hidden rest energy in accordance with Lorentz transformations. Umov’s continuum of field masses allows the local embedding of stored information in accordance with the Shannon distribution law to describe nonlocal hierarchies. The information guidance for the nonlocal mass integral nullifies its volumetric rest energy by self-gravity. Shannon entropy for big data can describe both macro- and mega-entanglement of correlated densities. Lomonosov’s interpretation “from here to there” for measured Newtonian forces supports instantaneous correlations in the matterspace informatics continuum of Umov, Kotel’nikov, and Shannon. Field mechanics of Russian cosmism proposes conceptual probes of monistic hierarchies with nonlocal entanglement for prospective use in energetics, engineering, informatics, life sciences, and astronomy.